Hiroshi Ishiguro: Android science and 'upstream engagement'. Issue 1 (1st March 2020) - Sone, Yuji
AbstractThis article discusses Hiroshi Ishiguro, a Japanese celebrity roboticist internationally acclaimed for his creation of androids. While his anthropomorphic machines are intended as models for future human-like robots, participating in work and domestic contexts, Ishiguro also regards them as experimental tools for investigations into questions of human identity. Beyond engineering challenges, he is not afraid to ask philosophical questions, such as 'what is the human?' Ishiguro has even had facial plastic surgery to match the appearance of his robot double, Geminoid HI-1. He has been described as the bad boy of Japanese robotics, an eccentric genius who is recognized as such in Japan, and overseas. While Ishiguro conducts scientific experiments, he has also deployed his anthropomorphic robots in popular entertainment contexts such as film, television, theatre and in museum exhibitions. Although Ishiguro's androids have almost always been included in mainstream western journalism's coverage concerning the development of next-generation robots in Japan, his anthropomorphic machines are often shown along with a photo of Ishiguro in his trademark black clothing, and described as 'freaky' and 'creepy'. I argue that Ishiguro's presentation feeds the western fascination with Japanese robot technology. This article examines the relationship between Ishiguro's larger-than-life public persona and his philosophy concerning his work as a kind of storytelling and upstream engagement in the context of robotic science.